2015
DOI: 10.1002/2014ja020912
|View full text |Cite
|
Sign up to set email alerts
|

Transpolar arc observation after solar wind entry into the high‐latitude magnetosphere

Abstract: Recently, Cluster observations have revealed the presence of new regions of solar wind plasma entry at the high-latitude magnetospheric lobes tailward of the cusp region, mostly during periods of northward interplanetary magnetic field. In this study, observations from the Global Ultraviolet Imager (GUVI) experiment on board the TIMED spacecraft and Wideband Imaging Camera imager on board the IMAGE satellite are used to investigate a possible link between solar wind entry and the formation of transpolar arcs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 56 publications
(114 reference statements)
2
22
0
Order By: Relevance
“…Fear et al [] also presented observation from Cluster that showed that the plasma source for this arc was on closed field lines. Similarly, a study by Mailyan et al [] presented observations of a transpolar arc (observed by IMAGE and the TIMED/GUVI instrument, which is very similar to SSUSI) and a conjugate in situ plasma signature detected by Cluster. The electron and ion signatures observed by Cluster were at lower energies than those observed by Fear et al [].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Fear et al [] also presented observation from Cluster that showed that the plasma source for this arc was on closed field lines. Similarly, a study by Mailyan et al [] presented observations of a transpolar arc (observed by IMAGE and the TIMED/GUVI instrument, which is very similar to SSUSI) and a conjugate in situ plasma signature detected by Cluster. The electron and ion signatures observed by Cluster were at lower energies than those observed by Fear et al [].…”
Section: Discussionmentioning
confidence: 77%
“…The electron and ion signatures observed by Cluster were at lower energies than those observed by Fear et al []. Mailyan et al [] were unable to determine whether the plasma and auroral signature observed were on open or closed magnetic field lines, but did identify fainter arcs in the GUVI image that branched away from the main transpolar arc. They also presented DMSP particle data with electron‐only signatures of comparable energy to our event, which are suggested to be associated with these fainter arcs.…”
Section: Discussionmentioning
confidence: 85%
“…Several subsequent studies have investigated this phenomenon further. Some have adopted the interpretation of direct solar wind entry proposed by Shi et al (2013): Mailyan et al (2015) reported a conjunction between plasma populations of the type observed by Shi et al (2013) and a transpolar arc, interpreted in the framework of direct solar wind entry, implicitly placing the transpolar arc on open magnetic field lines, and Gou et al (2016) performed a statistical analysis, arguing that observed dependencies could be explained by IMF control of the high latitude reconnection process. Others have sided with a closed field line topology formed by magnetotail reconnection: argued that if transpolar arcs are formed by magnetotail reconnection, then an observed interaction between a transpolar arc and the cusp spot (Frey et al 2002) indicated that the high latitude reconnection process (indicated by the presence of the cusp spot) was actually opening the closed magnetic flux associated with the transpolar arc.…”
Section: Source Of Polar Cap Arc Plasmasmentioning
confidence: 99%
“…However, other reports showed that the source particles are from dayside in the interaction region between the solar wind and magnetosphere (Chiu et al, 1985;Liou et al, 2005;Lyons, 1985;Yamamoto & Ozaki, 2005). In addition, the dayside and nightside parts of PCA with different source particles may be created by two different mechanisms, respectively (Eriksson et al, 2005;Mailyan et al, 2015). Recently, Reidy et al (2017) showed that both types of source particles (plasma sheet and polar rain) can be present in the polar cap at the same time and lead to PCAs at different local times.…”
Section: Introductionmentioning
confidence: 99%